Ultrastructural studies of seed coat and cotyledon during rapeseed maturation - Jian-bo CAO; Li-min HE; Chinedu Charles NWAFOR; Li-hong QIN; Chun-yu ZHANG; Yan-tun SONG; Rong HAO (Journal of Integrative Agriculture, 2021)
Brassica napus L. (B. napus) is an important oil crop worldwide and it rapidly accumulates oil at late stage of seed maturation. However, little is known about the cellular mechanism of oil accumulation and seed color changes during the late stage of rapeseed development. Here, we analyzed the ultrastructure of seed coat, aleurone and cotyledon in embryos of B. napus from 25 to 70 days after flowering (DAF). The pigments, which were deposited on the cell wall of palisade cells in seed coat, determined dark black color of rapeseed. The chloroplasts degenerated into non-photosynthetic plastids which caused the green cotyledon to turn into yellow. The chloroplasts in aleurone and cotyledon cells respectively degenerated into remnants without inner and outer envelope membranes and ecoplasts with intact inner and outer envelope membranes. From 40 to 70 DAF, there were degraded chloroplasts without thylakoid, oil bodies contacting with plastids or protein bodies, big starch deposits of chloroplasts degrading into small particles then disappearing, and small endoplasmic reticulum (ER) in aleurone and cotyledon cells. Additionally, there were decreases of chlorophyll content and dramatic increases of oil content in rapeseed. These results suggested that the rapid oil accumulation was independent on the NADPH synthesized by photosynthesis of chloroplasts and probably utilized other sources of reductant, such as the oxidative pentose phosphate pathway during the late stage of rapeseed development. The triacylglycerol assembly presumably utilizes the enzymes in the plastid, cytosol or oil body of cotyledon and aleurone cells.